Regulation of epidermal cell fate in Arabidopsis roots: the importance of multiple feedback loops - Schiefelbein, John; Zheng, Xiaohua; Huang, Ling (Frontiers in Plant Science, 2014)
The specification of distinct cell types in multicellular organisms is accomplished via establishment of differential gene expression. A major question is the nature of the mechanisms that establish this differential expression in time and space. In plants, the formation of the hair and non-hair cell types in the root epidermis has been used as a model to understand regulation of cell specification. Recent findings show surprising complexity in the number and the types of regulatory interactions between the multiple transcription factor genes/proteins influencing root epidermis cell fate. Here, we describe this regulatory network and the importance of the multiple feedback loops for its establishment and maintenance.